The Impact of the Development of Scientific Knowledge on Technological Progress through the Ages - Elatri, Abderrahim; Amari, Seddik Sadiki; Boulouh, Brahim (Dirasat: Human and Social Sciences, 2023)
Objectives: This article aims to monitor the dialectical relationship that exists between scientific knowledge and technology, by trying to reveal the link between them and to stand at the overlap and influence, and to highlight the limits of this relationship and its characteristics and scientific and social dimensions. Methods: the study adopted an analytical approach of a socio-anthropological nature. For this reason, the concept of knowledge and scientific knowledge were discussed, and a set of theoretical positions in different disciplines were called to show the impact of scientific knowledge on technological development through the ages. Results: Scientific research contributed greatly to building technology in general, and on the other hand, this technology is a clear reflection of all productions and perceptions of science and scientific knowledge. Conclusions: The study concluded the Technology Hip between knowledge and technology; Just as science intervenes to find solutions to some problems that may result from the improper use of technology, so the intervention of scientific research in its relationship with technical aspects, especially manufactured, is extremely important, in order to direct and correct the course of technological productions to be a source of comfort and happiness for humans, the Technology, in turn, has contributed greatly to the advancement of scientific research and has worked to achieve the latter's comfort and happiness.